Proses pembuatan Bilah pada Turbin Angin tipe taper dengan NACA Airfoil 6510 di PT. Lentera Bumi Nusantara - Ricky Ardiawan Berlyansyah; Oleh Oleh (Peneliti.net, 2022)
Wind energy is one of the most popular renewable energy alternatives. In the use of wind energy, of course, tools and technology are needed to process and process the energy conversion process. One technology that can be applied is wind turbines. Wind turbines are able to convert the kinetic energy of the wind into mechanical motion which is used to drive a generator that converts mechanical motion into electrical energy. From this case, the part of the windmill that plays a significant role in the process of converting wind energy is the blade. Therefore it is necessary to design a good blade based on field research so as to create a blade design that is able to work optimally according to the characteristics of the blade installation site. From the problems above, the authors are motivated to explore the process of making blades, and the process of making blades on the Wind Turbine is carried out with the Taper type with Airfoil NACA 6510 which consists of designing, selecting materials, machining processes. The material used for the process of making blades on the Taper Wind Turbing with Airfoil NACA 6510 is mahogany wood. The results of the process of making blades on a Taper Wind Turbine with Airfoil NACA 6510 obtained a radius of 0.8 m, linear chord from 0.113 – 0.70 m, torsion angle 12,580 – 5,580